2009
DOI: 10.1016/j.devcel.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Septins and the Lateral Compartmentalization of Eukaryotic Membranes

Abstract: Eukaryotic cells from neurons and epithelial cells to unicellular fungi frequently rely on cellular appendages such as axons, dendritic spines, cilia, and buds for their biology. The emergence and differentiation of these appendages depend on the formation of lateral diffusion barriers at their bases to insulate their membranes from the rest of the cell. Here, we review recent progress regarding the molecular mechanisms and functions of such barriers. This overview underlines the importance and conservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
255
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(265 citation statements)
references
References 119 publications
5
255
0
5
Order By: Relevance
“…The localization of C. reinhardtii septin to the base of the flagella is consistent with a possible role in barrier formation, which has been described to involve a structure known as the "flagellar bracelet" (39,40). Taken together, the in vitro and in vivo data point toward a probable role for CrSEPT in forming homopolymeric filaments that are organized at the base of the flagella to promote barrier formation.…”
Section: Reinhardtii Septin Localizes Mainly At the Base Of The Flsupporting
confidence: 65%
“…The localization of C. reinhardtii septin to the base of the flagella is consistent with a possible role in barrier formation, which has been described to involve a structure known as the "flagellar bracelet" (39,40). Taken together, the in vitro and in vivo data point toward a probable role for CrSEPT in forming homopolymeric filaments that are organized at the base of the flagella to promote barrier formation.…”
Section: Reinhardtii Septin Localizes Mainly At the Base Of The Flsupporting
confidence: 65%
“…This expression pattern suggests that SEPT7 may be involved in the regulation of the formation of the midpiece and annulus. Previous studies showed that SEPT1/4/6/7/12 are located at the sperm annulus and that this septin-based organization is a requisite for the structural and functional integrity of sperm [7,8,11,23]. Other proteins located at the mouse sperm annulus include DNAJB13 [24] and testis anion transporter 1 (TAT1) [25].…”
Section: Discussionmentioning
confidence: 99%
“…First, the septin rings serves as a scaffold for protein-protein interactions to recruit selective proteins at the site (Douglas et al, 2005;McMurray and Thorner, 2009). Second, septin rings function as a diffusion barrier across the plane of the mother-bud neck (Caudron and Barral, 2009). To date, 14 mammalian septin genes (SEPT1-14) have been identified (Cao et al, 2009;McMurray and Thorner, 2009).…”
Section: Introductionmentioning
confidence: 99%